Sialoglycans of skin derivatives of rat offspring on the 10th postnatal day of development at the background of experimental mercazolil-induced hypothyrosis of maternal organism. - Strus, Kh. I.; Yashchenko, A. M. (Морфологія / Morphologia / Morfologìâ, 2012)
With the use of sialo-specific lectins WGA and SNA, to investigate the role of sialoglycans in differentiation of structural components of skin derivatives in the offspring of control and hypothyrotic rats on the 10th postnatal day of development. Hypothyrosis was modeled by introduced with food mercazolil (5 mg/kg of body weight). Sliced skin taken from the back of offspring of control and hypothyrotic females were fixed in 4% neutral formalin and embedded in paraffin. Preparations 5-7 μm thick were stained with hematoxylin and eosin to study their general morphology. Lectin conjugates with horse-raddish peroxidase were used to identify carbohydrate determinants. Lectin receptors were visualized in the system 3́ 3-diaminobenzidin-H2O2. Reduced activity of metabolic processes at the background of thyroid hypofucntion in the maternal organism was noticed to be associated with reduced morphogenesis as well as slight decrease of the expression of sialoglycans that act as signal molecules and influencing growth processes and differentiation of structural components of skin derivatives.